Análise linguística da gagueira - Monica Medeiros de Britto Pereira (2001)
This work focus on the research of the alterations on the speech of stuttering adults and adolescents through analysis of the various kinds of disfluencies shown on their speech, from the linguistic point of view.This people were recorded, both on the video and DAT, on their spontaneous speech. Their sample speech were transcript orthographically, based on the video and on the DAT, divided in phrases that contain the disfluencies. The same phrases were edited based on the digital records and filled for acoustic analysis for measuring the length of the disfluencies. The disfluencies were analyzed in relation to length, kind, number of attempts, phone, size of the word, accent position, syllable structure, type of word (lexical or functional), position on the syllable, word and phrase. It was proposed a change on the name of some of the disfluencies, from "repetition" to " attempt". The data analyses was based on two basic strategies used by the stutters, that was the postponement of the word and the restart of the "problem" word and showed that the stuttering problem happens because of a momentary obstruction on the speech production, more precisely on the articulatory planning and is aggravated by emotional facts of this difficulty. The results that made this conclusion possible refer to the linguistic context where th disfluencies occur, more precisely the size of the word, type of word (lexical or functional), syllabic structure and position of the disfluency on the phrase, syllable and word. The analyses of the length of the disfluencies made it possible to discuss the aspect that refers to the prolongation. In relation to the phone the results shown that the disfluencies tend to occur more on the occlusive consonant. Finally, the analyses of some disfluency characteristics made it possible to establish a criteria for definition and differentiation among them, helping to englhten the stutter difficulties.